Answers

2015-07-05T20:44:10+05:30
Let,
daughter's age=x
father's age    =x+24

After 4years,
daughter's age=x+4
fathers age    = x+24+4

BUT acording to the sum
father's age will be 3times daughters age

so,
father's age = 3[daughter's age]
x+24+4       = 3[x+4]
x+28           = 3x + 12
x-3x            = 12-28
-2x        =   -16
that is 2x =16
     x=16/2
        
x=8
therefore fathers age is 24+x
                                   =24+8
                                  =32years
daughter's age =8years
0